Whole gene duplication of SCN2A and SCN3A is associated with neonatal seizures and a normal intellectual development. Issue 1 (2nd June 2016) - Thuresson, A‐C.; Van Buggenhout, G.; Sheth, F.; Kamate, M.; Andrieux, J.; Clayton Smith, J.; Soussi Zander, C.
Abstract : Duplications at 2q24.3 encompassing the voltage‐gated sodium channel gene cluster are associated with early onset epilepsy. All cases described in the literature have presented in addition with different degrees of intellectual disability, and have involved neighbouring genes in addition to the sodium channel gene cluster. Here, we report eight new cases with overlapping duplications at 2q24 ranging from 0.05 to 7.63 Mb in size. Taken together with the previously reported cases, our study suggests that having an extra copy of SCN2A has an effect on epilepsy pathogenesis, causing benign familial infantile seizures which eventually disappear at the age of 1–2 years. However, the number of copies of SCN2A does not appear to have an effect on cognitive outcome. Abstract : Whole gene duplications of SCN2A causes benign familial infantile seizures, but does not affect cognitive outcome.